Challenges of managing people with multimorbidity in today's healthcare systems. Issue 1 (December 2015) - Moffat, Keith; Mercer, Stewart
Abstract Multimorbidity is a growing issue and poses a major challenge to health care systems around the world. Multimorbidity is related to ageing but many studies have now shown that it is also socially patterned, being more common and occurring at an earlier age in areas of high socioeconomic deprivation. There is lack of research on patients with multimorbidity, and thus guidelines are based on single-conditions. Polypharmacy is common in multimorbidity, increasing drug-disease and drug-drug interactions. Multimorbid patients need holistic care, but secondary care services are highly specialised and thus are often duplicative and fragmented and thus increase treatment burden in multimorbid patients. The cost of care is high in multimorbidity, due to high rates of primary and secondary care consultations and unplanned hospital admissions. The combination of mental and physical conditions increases complexity of care, and costs. Mental-physical multimorbidity is especially common in deprived areas. General practitioners and primary care teams have a key role in managing patients with multimorbidity, using a patient-centred generalist approach. Consultation length and continuity of care may need to be substantially enhanced in order to enable such patients. This will require a radical change in how health care systems are organised and funded in order to effectively meet the challenges of multimorbidity.